2019
DOI: 10.5114/ms.2019.84050
|View full text |Cite
|
Sign up to set email alerts
|

Patient-related stressors and coping strategies in baccalaureate nursing students during clinical practice

Abstract: Introduction: The first clinical experience of nursing students is of great importance in their professional development and the formation of professional competence. The education process is a stressful experience. This is due to the large emotional commitment, responsibility for health and life, and struggling with the problems of patients. To fully benefit from this experience, it is necessary that students successfully cope with stress. Aim of the research: To assess patient-related stressors and coping be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…Almost half of the first-year students participating in our own research experienced intense stress. Similar conclusions were reached by Sun et al and Bodys-Cupak et al [18,19]. However, the results of research conducted on Norwegian students showed that only one third of the participants experienced high or average stress levels [20].…”
Section: Discussionsupporting
confidence: 80%
“…Almost half of the first-year students participating in our own research experienced intense stress. Similar conclusions were reached by Sun et al and Bodys-Cupak et al [18,19]. However, the results of research conducted on Norwegian students showed that only one third of the participants experienced high or average stress levels [20].…”
Section: Discussionsupporting
confidence: 80%
“…Globally, nursing is considered a very stressful profession ( 5 – 8 ). The high emotional burden associated with increasing workload in qualitative and quantitative terms, exposure to existing and emerging infectious diseases ( 9 ), the daily confrontation with the suffering of individuals and their families and low social support leads to many stress reactions among nurses ( 10 , 11 ). Indeed, studies by Allen and Shanock have shown that as they start their first job, young nurses experience enormous mental shock due to low social support and lack of socialization ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bodys-Cupaketal (2019) reported that as the stress level increased, the frequency of coping using avoiding behavior increased. They interpreted that the students in the difficult situations more often relied on problemfocused strategies rather than the emotion-focused strategies 21 . Shiferaw et al (2015) observed that the interpersonal, environmental, and academic stressors are closely linked to the unhealthy coping strategies 22 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a negative correlation was found related to the use of instrumental support; positive reframing; and acceptance. Bodys-Cupaketal (2019) noted that the students in the difficult situations ask for the social and instrumental support 21 . Bhurtun, etal (2019) indicated that nursing students managed stress using both problem-and emotion-based coping strategies 19 .…”
Section: Discussionmentioning
confidence: 99%